2020
DOI: 10.5935/1518-0557.20200009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Apoptosis and Quality of Sperm in Asthenozoospermia

Abstract: Objective: Vitamin D receptor (VDR) is expressed in human spermatozoa. However, the role of vitamin D (VD) in human male reproduction has not yet been clarified. In this study, effects of VD on sperm parameters and its apoptosis in asthenozoospermic and healthy men were evaluated. Methods: The study was carried out on discharged semen samples of 80 asthenozoospermic and healthy men. The samples were divided into control and experimental groups (received 20 µMol of VD). This study assessed sperm motility using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
(59 reference statements)
1
13
0
1
Order By: Relevance
“…As a result, they reported that VD3 has no effect on sperm normal morphology improvement; however, it could improve motility by decreasing apoptosis and sperm necrosis, especially in asthenozoospermic men. Therefore, it could be used for therapeutic opportunities [ 75 ]. Furthermore, the activation of Ca-dependent kinases and protein serine/threonine/tyrosine phosphorylation, the control of cell volume and osmolarity [ 60 ], and the improvement of integrity of sperm membrane by decreasing ROS [ 76 ], are known as some of the others proposed mechanisms for the increased sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they reported that VD3 has no effect on sperm normal morphology improvement; however, it could improve motility by decreasing apoptosis and sperm necrosis, especially in asthenozoospermic men. Therefore, it could be used for therapeutic opportunities [ 75 ]. Furthermore, the activation of Ca-dependent kinases and protein serine/threonine/tyrosine phosphorylation, the control of cell volume and osmolarity [ 60 ], and the improvement of integrity of sperm membrane by decreasing ROS [ 76 ], are known as some of the others proposed mechanisms for the increased sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the supplementation of a boar diet with 2000 IU/kg of vitamin D increased sperm motility [15]. In addition, vitamin D improved sperm viability [16], motility, early apoptosis, and necrotic of sperm were reduced in asthenozoospermic patients [17]. A study on human sperm revealed that adding vitamins to the sperm dilution medium could reduce the rate of apoptosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of VD has resulted in rise of motile sperm number, rise of progresive motility and reduced apoptosis and necrosis. However there were no morphology changes noticed [20].…”
Section: Review Of Available Researchmentioning
confidence: 87%